ESCALA AUDITIVA BINAURAL: validação de uma ferramenta de avaliação da satisfação considerando as pessoas com deficiência visual. - CAMPOS, Débora Regina Silva (2021)
Understanding user satisfaction in usability tests on digital interfaces is essential, as it points out the emotions felt during the interaction, offering important information for the development of new interfaces and systems. However, people with visual impairments have difficulty participating in tests of this nature because the tools used to collect data frequently used make it impossible for people with any degree of disability to participate because they are, for the most part, visual. So, the inclusion of these people in these tests is a key point, given that it is an audience that has used a lot of information and communication technologies in both the social and professional environments. To raise forms analogous to vision, a systematic review of the literature identified hearing as a sense similar to vision. In this perspective, a tool for collecting satisfaction data - Binaural hearing scale (3d audio) - was developed by Trinta (2020), whose purpose is to expand the participation of people with visual impairments in tests with users in the evaluation of digital interfaces. The results achieved in this research include the identification of some barriers encountered by the visually impaired in the use of smartphones, the main ones being the lack of reading of images by the screen reader. Another result covers the difficulties of this public POS in interacting with the existing tools used to understand satisfaction and emotions in tests with users, in which the use of SUS was identified as the difficulty in handling questionnaires in braille, and the inconsistency in the use of some terms; in relation to the onomatopoeic tool, it was perceived a lot of difficulty for the identification of emotions. In view of this, the following question was raised: What is the reliability and validity of the binaural hearing scale (3d audio) to assess the satisfaction of people with visual impairments in usability tests? Thus, the objective of the present research is to validate the prototype of the Binaural Auditory Scale Tool (3d audio) through Cronbach's Alpha and the survey of the perception of people with visual impairments regarding its relevance and effectiveness. The research validated the 3D hearing tool to assess satisfaction in usability tests using Cronbach's Alpha, whose result was acceptable. It is concluded that the 3D Hearing Tool is efficient to assess satisfaction and that the use of 3D audio improves the identification of emotions. For visually impaired people, the developed tool gives an opportunity to give an opinion on their satisfaction in usability tests. For developers it presents itself as an option for testing interfaces or products considering the participation of people with visual impairments.